Determinants of Islamic Social Reporting: Analysis of the Characteristics of Energy Companies in Indonesia - Sandra Sukma Embuningtiyas; Oktaviani Ritas Puspasari (Faculty of Islamic Economics and Business UIN Salatiga, 2025)
This study aims to obtain evidence regarding the factors influencing the level of Islamic Social Responsibility disclosure in energy companies. The population of this study were energy companies listed on the Indonesian Sharia Stock Index, covering the period 2019-2023. The sample was determined using a purposive sampling technique and a sample size of 20 companies. Data were analyzed using a panel regression with a fixed effect approach. The company characteristics tested included environmental performance, profitability, leverage, firm size, and good corporate governance mechanisms. Control variables were firm age and the COVID-19 pandemic. The results showed that environmental performance, profitability, firm size, and good corporate governance significantly influenced Islamic social responsibility. Meanwhile, leverage, firm age, and the COVID-19 pandemic did not influence Islamic social responsibility. This finding is in line with legitimacy theory, which states that companies disclose Islamic social responsibility (ISR) to maintain a positive public perception. This finding is also in line with sharia enterprise theory, which explains that good internal company characteristics will encourage accountability to God, humans, and the environment through ISR disclosure. The results of this study also strengthen stakeholder theory, where companies respond to stakeholder demands for transparency and social responsibility through ISR disclosure.